EFFECTS OF VITAMIN D IN NEONATES AND YOUNG INFANTS: AN UPDATED SYSTEMATIC REVIEW - Erdiana, Grace; Glenardi, (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Vitamin D is a fat-soluble vitamin essential for calcium metabolism, maintaining calcium homeostasis, and supporting skeletal mineralization. Low maternal levels of vitamin D during pregnancy are linked to various adverse neonatal outcomes. This study aims to systematically review the effects of Vitamin D in neonates and infants in literatures of the last 5 years.  Methods: The systematic review followed PRISMA 2020 standards and examined full-text English literature published between 2019 and 2024. This review excluded editorials, review papers from the same journal, and submissions without a DOI. Literature was sourced from online platforms such as PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of  2,866 articles were retrieved from online databases (PubMed, SagePub, SpringerLink and Google Scholar). After three rounds of screening, four articles directly relevant to the systematic review were selected for full-text reading and analysis. Conclusion: Vitamin D is essential for skeletal, immune, and neurodevelopmental health in children. Maternal supplementation during pregnancy is crucial for ensuring adequate levels in infants and neonates, along with promoting sunlight exposure and dietary intake, particularly in regions with high rates of maternal vitamin D deficiency.